Analysis of high school students’ interest in participating in volleyball extracurricular activities - Yuliana Fatubun; Achmad Nuryadi; Angga Indra Kusuma; Eka Kurnia Darisman (Universitas Sriwijaya, 2025)
Research Problems: Over the past year, the performance of the volleyball extracurricular program at SMA ITP Surabaya has declined, followed by a decrease in student participation. This suggests a drop in interest that requires further investigation. Research Objectives: This study aims to analyse students’ interest in participating in the volleyball extracurricular activity and to identify intrinsic and extrinsic factors influencing their participation through questionnaires and interviews. Method: A qualitative descriptive approach was employed. Data were collected using questionnaires and interviews to provide a comprehensive overview of student interest levels. Results: Findings reveal that students’ intrinsic interest reached only 8.25% (categorised as very good). In comparison, extrinsic interest accounted for 61.87% (categorised as good), indicating that external factors play a more significant role in influencing participation. Conclusion: Extrinsic factors are more dominant in shaping students’ interest in volleyball extracurricular activities, highlighting the importance of strengthening external support to boost engagement.